The application of electrolytic photoetching and photopolishing to AISI 304 stainless steel and the electrolytic photoetching of amorphous cobalt alloy - Talib, Talib Naji (Cranfield University, 1986)
The results presented cover broad aspects of a quantitative investigation into the elecrolytic etching and polishing of metals and alloys through photographically produced dielectric stencils (Photoresists). A study of the potential field generated between a cathode and relatively smaller anode sites as those defined by a dielectric stencil was carried out. Numerical, analytical and graphical methods yielded answers to the factors determining lateral dissolution (undercut) at the anode/stencil interface. A quasi steady state numerical model simulating the transient behavior of the partially masked electrodes undergoing dissolution was obtained. AISI 304 stainless steel was electrolytically photoetched in 10% w/w HC1 electrolyte. The optimised process parameters were utilised for quantifying the effects of galvanostatic etching of the anode as that defined by a relatively narrow adherent resist stencil. Stainless steel was also utilised in investigating electrolytic photopolishing. A polishing electrolyte (orthophosphoric acid —glycerol) was modified by the addition of a surfactant which yielded surface texture values of 70nm (Ra) and high levels of specular reflectance. These results were used in the production of features upon the metal surface through photographically produced precision stencils. The process was applied to the production of edge filters requiring high quality surface textures in precision recesses. Some of the new amorphous material exhibited high resistance to dissolution in commercially used spray etching formulations. One of these materials is a cobalt based alloy produced by chill block spinning. This material was also investigated and electro etched in 10% w/w HC1 solution. Although passivity was not overcome, by selecting suitable operating parameters the successful electro photoetching of precision magnetic recording head laminations was achieved. Similarly, a polycrystalline nickel based alloy also exhibiting passivity in commercially used etchants was successfully etched in the above electrolyte.